Gendered beginnings - Gendered Beginnings, (2001 : Queensland); Central Queensland University. Gender Research Group (Rockhampton : Gender Research Group, 2003)
"The One-Day Conference, Gendered Beginnings, was held at Central Queensland University on March 1st 2001. It was the first conference of this new group."
Title from title screen (viewed on 4 Nov. 2003).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://transformations.cqu.edu.au/conferences/2001/articles/text.html
System requirements: Adobe Acrobat for viewing pdf files.
Selected for archiving
Keywords: Gender identity -- Congresses; Sex role -- Congresses